Respuesta :

x-2 = 3(x-4)

First we should simplify "3(x-4)" .... 3x-12

Now we have : x-2 = 3x-12

Then we should isolate the x and leave it on one side by itself, to do this we can subtract x from both sides and add the 12 to both, doing this we get:

10=2x

Then we should divide the 2 to both sides and we end up with:

x=5

x - 2 = 3(x - 4)

Distribute 3 inside the parentheses.

x - 2 = 3x - 12

Add 2 to both sides.

x = 3x - 10

Subtract 3x from both sides.

-2x = -10

Divide both sides by -2.

x = 5

ACCESS MORE